Pengaruh Financial Difficulty Level, Growth Opportunity, Company Size, Leverage dan Profitabilitas terhadap Konservatisme Akuntansi - Pratiwi, Dea; Zulfikar, Zulfikar (Journal of Accounting and Finance Management, 2024)
This study aims to analyze the effect of financial difficulty level, growth opportunity, company size, leverage, and profitability on accounting conservatism. This type of research is a quantitative method. The population in this study was obtained from data from non-financial companies that publish financial statements and annual reports on the Indonesia Stock Exchange (IDX) and the company's official website for the period 2020-2022. This research data is secondary obtained through direct access on the website of Indonesia Stock Exchange (IDX) (www.idx.com) and the company's official website. Sampling method using purposive sampling, and obtained the final results of the company as a sample of 552 companies.  The method of analysis used is multiple linear regression analysis. The results provide empirical evidence that financial difficulty level, growth opportunity, company size, leverage does not affect the accounting conservatism, while profitability affects the accounting conservatism